INDONESIAN MIGRANT WORKER PROTECTION: THE ROLE OF BNP2TKI TO PROTECT INDONESIAN MIGRANT WORKER IN SAUDI ARABIA 2016 POST MORATORIUM - wahyu premono sudewo (UNIDA GONTOR, 2018)
Indonesia is one of the developing countries. Thus the government of Indonesia should strive in advancing the Indonesian economy. One of the Indonesian Government's strategies in advancing the Indonesian economy is the distribution of Indonesian Migrant Workers abroad. The national agency which assigned to the placement of Indonesian workers is BNP2TKI. With many problems against Indonesian Migrant Workers in Saudi Arabia, Indonesian Government makes the policy to the distribution of Indonesian Migrant Workers in the form decree of the Ministry of Manpower of the Republic Indonesia Number 260 in 2015. The Minister of Manpower policy is the Moratorium of Indonesian Migrant Workers to the Middle East Region, especially Saudi Arabia. The role of the Indonesian Government towards Indonesian Migrant Workers is to provide protection and fulfill their rights as citizens so that the distribution of individual Indonesian workers is banned. It aims to keep Indonesian citizens working abroad and fulfillment of the right to Indonesian Migrant Workers. Theory of Legal Protection relates to laws governing the protection of Indonesian workers abroad in accordance with Indonesian law, while the concept of human rights relates to the rights that Indonesian Workers are getting which is correlated with ad-dhuriyat or the fulfillment of rights in Islam. The role of the Indonesian government is important to the protection of Indonesian Migrant Workers, BNP2TKI as a National Institution in charge of protecting Indonesian Migrant Workers abroad have policies to Indonesian Migrant Workers abroad, the policies regulated by the Indonesian manpower minister are then developed by BNP2TKI in making policies against Indonesian Migrant Workers in Saudi Arabia, the policies are undertaken by BNP2TKI, there is no distribution of Indonesian individual Migrant Workers in Saudi Arabia in accordance with the provisions of the Minister of Manpower, the Indonesian Formal Migrant Workers can still be distributed except for women's cleaning service,. Government efforts in the protection of Indonesian Migrant Workers in Saudi Arabia are effective and will be more effective if the Indonesian government makes agreements with recipient countries of the Indonesian Migrant Workers on the protection of Indonesian Migrant Workers.